Competition and risk‐taking in investment banking. Issue 2 (5th March 2019) - Degl'Innocenti, Marta; Fiordelisi, Franco; Girardone, Claudia; Radić, Nemanja
Abstract: How does competition affect the investment banking business and the risks individual institutions are exposed to? Using a large sample of investment banks operating in seven developed economies over 1997–2014, we apply a panel VAR model to examine the relationships between competition and risk without assuming any a priori restrictions. Our main finding is that investment banks' higher risk exposure, measured as a long‐term capital‐at‐risk and return volatility, was facilitated by greater competitive pressures for both boutique investment banks and full‐service investment banks. Overall, we find some evidence that more competition leads to more fragility before and during the recent financial crisis.